Dickens and popular entertainment - Schlicke, Paul (Allen & Unwin, 1985)
Dickens and Popular Entertainment is the first extended study of this vital aspect of Dicken's life and work. Ranging widely through showmen's memoirs, playbills, advertisements, journals, drawings and imaginative literature, Paul Schlicke explores the ways in which Dickens channelled his love of entertainment into incomparable artistry. Circus, fair, theatre and street performances provided the novelist with subject matter and with the sources of imaginative stimulus essential to his art. Splendidly illustrated with nineteenth-century engravings, many reprinted here for the first time, this s.